Mitochondrial calcium uniporter blocker prevents cardiac mitochondrial dysfunction induced by iron overload in thalassemic mice - Kumfu S. (Springer Netherlands, 2015)
Iron-overload induced cardiomyopathy is a major cause of morbidity and mortality in thalassemic patients. Previous studies suggest that cardiac mitochondrial dysfunction may be involved in the pathogenesis of cardiomyopathy in thalassemia. We tested the hypothesis that iron overload causes dysfunction of cardiac mitochondria isolated from thalassemic mice. Cardiac mitochondria were isolated from the heart tissue of genetically-altered, β-thalassemic mice (HT) and adult wild-type mice (WT). Ferrous iron (Fe2+) at various concentrations (0-5 μg/ml) was applied to induce iron toxicity. Pharmacological interventions, facilitated by mitochondrial permeability transition pore (mPTP) blocker, CsA, and mitochondrial Ca2+ uniporter (MCU) blocker, Ru360, were used to study their respective effects on cardiac mitochondrial dysfunction. Cardiac mitochondrial ROS production, mitochondrial membrane potential changes, and mitochondrial swelling were determined. Iron overload caused increased ROS production, mitochondrial depolarization, and mitochondrial swelling in a dose-dependent manner in WT and HT cardiac mitochondria. CsA decreased only ROS production in WT and HT cardiac mitochondria, whereas Ru360 completely prevented the development of cardiac mitochondrial dysfunction by decreasing ROS, mitochondrial depolarization, and swelling in both WT and HT cardiac mitochondria. Ru360, an MCU blocker, provides protective effects by preventing ROS production and mitochondrial depolarization as well as attenuating mitochondrial swelling caused by Fe 2+ overload. These findings indicate that the MCU could be a major portal for Fe2+ entry into cardiac mitochondria. Therefore, blocking MCU may be an effective therapy to prevent iron-overload induced cardiac mitochondrial dysfunction in patients with thalassemia. Copyright © Springer Science+Business Media, LLC. 2012.